Involvement of the Polypyrimidine Tract-Binding Protein-Associated Splicing Factor (PSF) in the Hepatitis Delta Virus (HDV) RNA-Templated Transcription - Zhang, Da Jiang (Université d'Ottawa / University of Ottawa, 2014)
Hepatitis delta virus (HDV) is the smallest known mammalian RNA virus, containing a genome of ~ 1700 nt. Replication of HDV is extremely dependent on the host transcription machinery. Previous studies indicated that RNA polymerase II (RNAPII) directly binds to and forms an active preinitiation complex on the right terminal stem-loop fragment (R199G) of HDV genomic RNA, and that the polypyrimidine tract-binding protein-associated splicing factor (PSF) directly binds to the same region. Further studies demonstrated that PSF also binds to the carboxyl-terminal domain (CTD) of RNAP II. In my thesis, co-immunoprecipitation assays were performed to show that PSF stimulates the interaction of RNAPII with R199G. Results of co-immunoprecipitation experiments also suggest that both the RNA recognition motif 2 (RRM2) and N-terminal proline-rich region (PRR) of PSF are required for the interaction between PSF and RNAPII, while the two RNA recognition motifs (RRM1 and RRM2) might be required for the interaction of PSF with R199G. Furthermore, in vitro run-off transcription assays suggest that PSF facilitates the HDV RNA transcription from the R199G template. Together, the above experiments suggest that PSF might act as a transcription factor for the RNAPII transcription of HDV RNA by linking the CTD of RNAPII and the HDV RNA promoter. My experiments provide a better understanding of the mechanism of HDV RNA-dependent transcription by RNAP II.
Keywords: Hepatitis delta virus; RNA polymerase II; RNA promoter; Polypyrimidine tract-binding protein-associated splicing factor PSF / SFPQ; Co-immunoprecipitation; RNA recognition motif RRM; Proline-rich region PRR; Carboxyl-terminal domain CTD; Transcription